Chemical warfare simulant‐responsive polymer nanocomposites: Synthesis and evaluation. Issue 18 (23rd March 2017) - Sha, Sheng‐Chun; Zhu, Rong; Herbert, Myles B.; Kalow, Julia A.; Swager, Timothy M.
ABSTRACT: Nanomaterials that undergo a physical change upon chemical warfare agent (CWA) exposure can potentially be used in detectors to warn soldiers of their presence or in fabrics to provide on‐demand protection. In this study, hybrid nanoparticles (NPs) were prepared by grafting a CWA‐responsive polymer from a silicon dioxide (SiO2 ) surface using ring opening metathesis polymerization; the covalent functionalization of the polymers on the NP surface was confirmed by gel permeation chromatography, dynamic light scattering, and transmission electron microscopy analysis. The polymer‐grafted SiO2 NPs were found to undergo a pronounced decrease (approximately 200 nm) in their hydrodynamic radius upon exposure to CWA simulants trifluoroacetic acid and diethyl chlorophosphate in toluene. This decrease in hydrodynamic radius is attributed to the electrophile‐mediated ionization of the triarylmethanol responsive unit and represents a rare example of polycation formation leading to polymer chain collapse. We have ascribed this ionization‐induced collapse to the formation of a favorable stacking interaction between the planar triarylcations. These studies have important implications for the development of breathable fabrics that can provide on‐demand protection for soldiers in combat situations. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3034–3040 Abstract : Chemical warfare agents continue to post a threat to civilians and military personnel in conflict zones. As a step toward a breathable hybrid fabric that provides on‐demand protection against these agents, the authors have synthesized a triarylmethanol‐containing responsive polymer‐substituted nanoparticle using surface‐initiated ring‐opening metathesis polymerization. Using this nanocomposite as a platform demonstrates a tunable chain collapsing response upon exposure to agent simulants, which is the key to the proposed protecting scheme.